2015
DOI: 10.1111/modl.12191
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Context and Cognitive Effort in Vocabulary Learning: A Study of Intermediate‐Level Learners of Arabic

Abstract: Despite years of research on vocabulary learning and teaching, relatively little is known about strategies for effective mastery of vocabulary in less commonly taught languages. The current study focuses on English native speakers studying Modern Standard Arabic to identify effective ways to present and learn new vocabulary using tasks varying in the degree of lexical context provided and the amount of cognitive effort needed to complete them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 27 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…The results suggested that learning the words in isolation was better than with context. Similar results were found by Golonka et al (2015). Their learners were presented with 60 target words learned across six sessions.…”
Section: Contextualized Learning Of Wordssupporting
confidence: 76%
“…The results suggested that learning the words in isolation was better than with context. Similar results were found by Golonka et al (2015). Their learners were presented with 60 target words learned across six sessions.…”
Section: Contextualized Learning Of Wordssupporting
confidence: 76%
“…Notes 1. The term semi-contextualized is used to describe a task providing short written contexts, rather than a vocabulary task embedded in a longer passage (Golonka et al, 2015). 2.…”
Section: Discussionmentioning
confidence: 99%
“…Elgort and Warren's (2014) study supported the findings, revealing that chances of robust learning were higher for more concrete lexical items. Golonka, et al (2015) discussed the role of lexical context for native English speakers in learning Arabic L2 vocabulary. Overall, the study suggested learning vocabulary from reading for comprehension was less effective than learning from vocabulary-focused decontextualized or semi-contextualized tasks.…”
Section: What Types Of Vocabulary Are Easier To Be Inferred Through Cmentioning
confidence: 99%
“…Mestres-Missé, et al, 2014 1) Concrete word meanings were discovered and learned faster than abstract word meanings even when matched on context availability; 2) Chances of robust learning were higher for more concrete lexical items. Golonka, et al, (2015), The Modern Language Journal.…”
Section: What Types Of Vocabulary Are Easier To Be Inferred Through Cmentioning
confidence: 99%